HLA B subtype analysis in patients developing tuberculosis during anti-TNF treatment - Fatih Albayrak; Gökhan Keser; Serdar Oztuzcu; Belkıs Nihan Coşkun; Yavuz Pehlivan; Tuba Demirci Yıldırım; Gökçe Kenar Artın; Gözde Çetin Yıldırım; Bünyamin Kısacık (Scientific Reports)
Abstract In this study, we aimed to evaluate HLA-B subtypes in cases developing TB while using anti-TNF agents and to compare with the HLA-B subtypes of three different groups including community-acquired TB cases, anti-TNF patients without TB and healthy controls. The study consisted of four groups. Group 1: 35 community-acquired TB patients, group 2; 47 anti-TNF-TB patients, group 3; 61 anti-TNF (non TB) patients and group 4; 40 healthy controls. HLA-B subgroups were studied genetically from blood samples taken from the patients. Approval was received from the ethics committee. HLA-B typing was performed by using the LIFECODES HLA-B eRES SSO Typing SSO typing kit (Immucor, Stamford, CT, USA). Among HLA-B subtypes, significant differences between the four groups were found only for HLA-B5, HLA-B8, HLA-B27 and HLA-B38. Although frequency of HLA-B8 was highest in patients developing TB during anti-TNF treatment, significance was lost after Bonferoni correction. HLA-B27 was significantly higher in both anti-TNF groups, with and without TB, due to presence of patients with ankylosing spondylitis in those groups. To our knowledge, this is the first study analyzing HLA-B subtypes in anti-TNF patients developing TB. Although in literature HLA-B8 positivity was suggested to associate with or to confer a risk for community-acquired TB, we could not confirm this association in anti-TNF patients developing TB. However, further studies with larger number of patients from different ethnic groups are clearly needed to get the final word in this topic.